Parametric Finite Element Method-Based Analysis of Curved Sandwich Structures under Projectile Impact - Bagaskara, Galang; Arifvianto, Budi; Mahardika, Muslim; Mao, Zebing; Wiranata, Ardi (Faculty of Engineering and Technology, Sampoerna University, 2025)
This study aims to develop a Python and Gmsh-based program for automating the generation of finite element method (FEM) models and integration with the OpenRadioss solver, enabling more efficient creation of a FEM model for a curved corrugated sandwich structure under projectile impact. Based on the research conducted, the program has been successfully integrated with OpenRadioss and successfully simulated. The simulation results show a graph that closely matches experimental data, indicating that the generated finite element model is acceptable. The time required to generate the model is approximately ±73 s, while conventional methods require at least ±480 s. Additionally, this program has been compared with the latest Graphical User Interfaces (GUI) provided by OpenRadioss, demonstrating the advantages of the developed program in terms of time efficiency, ease of use, and its ability to handle design variations more quickly.